Diagnostic concordance between whole slide imaging and conventional light microscopy in cytopathology: A systematic review. Issue 1 (10th October 2019) - Girolami, Ilaria; Pantanowitz, Liron; Marletta, Stefano; Brunelli, Matteo; Mescoli, Claudia; Parisi, Alice; Barresi, Valeria; Parwani, Anil; Neil, Desley; Scarpa, Aldo; Rossi, Esther Diana; Eccher, Albino
Abstract : Many studies have examined the diagnostic concordance of whole slide imaging (WSI) and light microscopy (LM) for surgical pathology. In cytopathology, WSI use has been more limited, mainly because of technical issues. The aim of this study was to review the literature and determine the overall diagnostic concordance of WSI and LM in cytopathology. A systematic search of PubMed, Scopus, and the Cochrane Library was performed, with data extracted from the included articles. A quality assessment of studies was performed with a modified Quality Assessment of Diagnostic Accuracy Studies 2 tool. The primary outcome was concordance for the diagnoses rendered by WSI and LM as shown by the concordance rate with the original diagnosis, intra‐observer and interobserver concordance with the κ coefficient, or a percentage. Secondary outcomes included the time taken to reach a diagnosis and the quality and perception of WSI. A descriptive survey was provided. Among 1867 publications, a total of 19 studies (1%) were included. Overall, the concordance between WSI and the original diagnosis was 84.1%, the intra‐observer concordance between WSI and LM was 92.5% with a κ coefficient of 0.66, and the interobserver κ coefficient was 0.69. The time to reach a diagnosis was longer with WSI in all studies. The quality of WSI was good, but diagnostic confidence and cytologist preference were higher for LM. In conclusion, the concordance of WSI with LM is acceptable and in line with systematic reviews in surgical pathology. However, the time required for scanning and technical issues represent barriers to complete adoption. It is foreseeable that technical advances and rigorous validation study design will help to improve the diagnostic concordance of WSI with LM in cytopathology. Abstract : The diagnostic concordance of whole slide imaging with light microscopy in cytopathology as measured with the intra‐observer κ coefficient is comparable to that of surgical pathology. Some limitations due to the scan time and the time to render a diagnosis can be still barriers to the widespread adoption of whole slide imaging in cytopathology.